Cyclodextrin‐Based Supramolecular Assemblies and Hydrogels: Recent Advances and Future Perspectives. Issue 13 (8th April 2014) - Tan, Shereen; Ladewig, Katharina; Fu, Qiang; Blencowe, Anton; Qiao, Greg G.
<x xml:space="preserve">Abstract</x> The application of cyclodextrin (CD)‐based host–guest interactions towards the fabrication of functional supramolecular assemblies and hydrogels is of particular interest in the field of biomedicine. However, as of late they have found new applications as advanced functional materials (e.g., actuators and self‐healing materials), which have renewed interest across a wide range of fields. Advanced supramolecular materials synthesized using this noncovalent interaction, exhibit specificity and reversibility, which can be used to impart reversible cross‐linking, specific binding sites, and functionality. In this review, various functional CD‐based supramolecular assemblies and hydrogels will be outlined with the focus on recent advances. In addition, an outlook will be provided on the direction of this rapidly developing field. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>